Fractal Analysis of Long Laboratory Sparks of high Speed Video Recordings - Vayanganie, A.; Gunasekera, L.; Fernando, M.; Sonnadara, U.; Cooray, V.; Rahman, M.; Hettiarachchi, P.; Diaz, O. (ICLP, 2016)
Variation of fractal dimension of long laboratory sparks were studied using high speed video recordings and still images. Four sparks were selected for the study, including both positive and negative polarities in lightning and switching impulses. Temporal and spatial variation of fractal dimension was studied. It was found that the fractal dimension is maximum at the breakdown. No particular pattern was observed for the variation of fractal dimension along the channel. Results show that the value of fractal dimension depends on the angle of view.
Keywords: Lightning